2020
DOI: 10.17522/balikesirnef.741401
|View full text |Cite
|
Sign up to set email alerts
|

TIMSS 2015 Türkiye Örnekleminde Matematik Başarı Testine Dayalı Olarak Öğrencilerin Bilişsel Tanı Modelleri İle Sınıflandırılması

Abstract: The aim of this study is to examine the classification of students in accordance with different attributes on the basis of mathematics test data in TIMSS 2015 Turkey sample. For this purpose, DINA and DINO models were used from Cognitive Diagnosis Models. Four different Q-Matrices were determined as the levels of the content domain (numbers, data display, geometric shapes and measures), the levels of the cognitive domain (knowing, applying, reasoning), the levels of both the content and the cognitive domain, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There are various studies in the literature that focus on TIMSS mathematics cognitive domain skills and levels. For instance, Gündüz and Çakan (2020) examined the learning outcomes in the middle school mathematics curriculum based on TIMSS cognitive domain skills, considering both grade levels and learning outcomes. The findings revealed that the cognitive levels of the learning outcomes varied across grades, with the highest proportion of knowing level outcomes observed in the 5th grade.…”
Section: Conceptual Framework About Timss Mathematics Cognitive Area ...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are various studies in the literature that focus on TIMSS mathematics cognitive domain skills and levels. For instance, Gündüz and Çakan (2020) examined the learning outcomes in the middle school mathematics curriculum based on TIMSS cognitive domain skills, considering both grade levels and learning outcomes. The findings revealed that the cognitive levels of the learning outcomes varied across grades, with the highest proportion of knowing level outcomes observed in the 5th grade.…”
Section: Conceptual Framework About Timss Mathematics Cognitive Area ...mentioning
confidence: 99%
“…For example, when the international literature is examined, it is observed that studies have been conducted to examine the relationship between academic achievement in school mathematics and achievement in the TIMSS mathematics subtest (Wiberg, 2019) and the factors that affect students' achievement in the TIMSS mathematics subtest (Dodeen, Abdelfattah, Shumrani, & Hilal, 2012). Additionally, there are studies that investigate the gender factor in TIMSS mathematics subtest achievement (Cheng & Seng, 2001) and whether the mathematics curricula implemented in countries are compatible with the content of the TIMSS When examining the researches conducted on the TIMSS mathematics subtest in our country, studies examining the compatibility of examples in math textbooks or the achievements in math curricula with the learning areas and cognitive levels in TIMSS mathematics tests are among the leading studies (Delil, Özcan, & Işlak, 2020;Gündüz & Çakan, 2020;Güner, 2015;İncikabı, Mercimek, Ayanoğlu, Aliustaoğlu, & Tekin, 2016;Kılıç, Aslan Tutak, & Ertaş, 2014;Taşpınar-Şener & Bulut, 2022;Toptaş, Elkatmış, & Karaca, 2012). In addition, studies comparing math exam questions (Taştekinoğlu & Aydın, 2014) or questions in the math subtests of large-scale national exams with questions in the TIMSS mathematics test (Yolcu Tetik & Delil, 2015) are also among these studies.…”
Section: Importance Of the Studymentioning
confidence: 99%